Komposit Berpenguat Serat Resam dengan Uji Tarik sebagai Material pada Pembuatan Joran Pancing - Abdallah, Fajar; Rollastin, Boy; harwadi, harwadi (Jurnal Teknologi, 2025)
This research aims to obtain the appropriate composition in the production of alternative materials for fishing rods with fiber-resin reinforcement, as well as to determine the tensile and bending test results for the alternative material to be used as fishing rods. This study uses a full factorial method to determine the number of spesimens to be made, with variations in fiber-resin composition: the number of fibers used is 5, 10, and 15 strands, with a resin-to-catalyst ratio of 50:1 and drying times of 1 hour, 2 hours, and 3 hours. Tensile strength tests were performed on 9 spesimens with 3 replications, and bending tests were conducted on 9 spesimens with 3 replications per spesimen, resulting in a total of 54 spesimens tested. Based on the best tensile test results, the spesimen with 15 strands of fiber soaked for 2 hours in a 5% NaOH solution achieved a tensile strength of 46.2 MPa, while the lowest tensile strength was obtained from the spesimen with 5 strands of fiber soaked for 2 hours, which was 19.9 MPa. The average tensile test results showed a maximum value of 38.4 MPa